Circumcircles

Circumcircles

A LevelEdexcel

Circumcircles

(Note: This topic is Edexcel only.)

Circumcircles are circles that touch all three points of a triangle. To find a triangle’s circumcircle combines all of the skills of geometry, including circle theorems, perpendicular bisectors, midpoints, lengths and finally forming the equation of a circle.

A Level Edexcel

The Circumcircle

A circumcircle is a circle that passes through all three vertices of a triangle. You may need to find the equation of a circumcircle given the three points of a triangle.

Notice that the perpendicular bisectors of the sides of the triangle all meet at the centre – this is because the perpendicular from the centre to a chord bisects the chord, and all of the sides of the triangle are chords.

This means that, to find the centre of the circle, simply find two of the perpendicular bisectors of the sides of the triangle, and find where they intersect.

Then, the radius is simply the distance from the centre to one of the corners of the triangle.

A LevelEdexcel
A Level Edexcel

Example: Equation of a Circumcircle

A triangle has vertices (1,1),(2,3),(0,5). Find the equation of its circumcircle.

[8 marks]

Step 1: Find equation of the perpendicular bisector of the line through (1,1) and (2,3).

\begin{aligned}\text{gradient}&=\dfrac{3-1}{2-1}\\[1.2em]&=\dfrac{2}{1}\\[1.2em]&=2\end{aligned}

So gradient of perpendicular bisector is \dfrac{-1}{2}

\begin{aligned}\text{m.point}&=\left(\dfrac{1+2}{2},\dfrac{1+3}{2}\right)\\[1.2em]&=\left(\dfrac{3}{2},\dfrac{4}{2}\right)\\[1.2em]&=\left(\dfrac{3}{2},2\right)\end{aligned}

So the perpendicular bisector goes through the point \left(\dfrac{3}{2},2\right)

Now use all of this information to generate the equation of a line in the form y=mx+c:

y-y_{1}=m(x-x_{1})

y-2=\dfrac{-1}{2}(x-\dfrac{3}{2})

y-2=-\dfrac{1}{2}x+\dfrac{3}{4}

y=-\dfrac{1}{2}x+\dfrac{3}{4}+2

y=-\dfrac{1}{2}x+\dfrac{11}{4}

 

Step 2: Find equation of the perpendicular bisector of the line through (2,3) and (0,5).

\begin{aligned}\text{gradient}&=\dfrac{5-3}{0-2}\\[1.2em]&=\dfrac{2}{-2}\\[1.2em]&=-1\end{aligned}

So gradient of perpendicular bisector is 1

\begin{aligned}\text{m.point}&=\left(\dfrac{2+0}{2},\dfrac{3+5}{2}\right)\\[1.2em]&=\left(\dfrac{2}{2},\dfrac{8}{2}\right)\\[1.2em]&=(1,4)\end{aligned}

So the perpendicular bisector goes through the point (1,4)

Now use all of this information to generate the equation of a line in the form y=mx+c:

y-y_{1}=m(x-x_{1})

y-4=x-1

y=x-1+4

y=x+3

 

Step 3: Find centre by finding where the perpendicular bisectors intersect.

y=-\dfrac{1}{2}x+\dfrac{11}{4}

y=x+3

x+3=-\dfrac{1}{2}x+\dfrac{11}{4}

\dfrac{3}{2}x+3=\dfrac{11}{4}

\dfrac{3}{2}x=\dfrac{11}{4}-3

\dfrac{3}{2}x=-\dfrac{1}{4}

x=-\dfrac{2}{3}\times\dfrac{1}{4}

x=-\dfrac{2}{12}

x=\dfrac{-1}{6}

y=x+3

y=-\dfrac{1}{6}+3

y=\dfrac{17}{6}

So centre is \left(\dfrac{-1}{6},\dfrac{17}{6}\right)

 

Step 4: Find the radius of the circumcircle by finding the distance from one corner to the centre.

Here we use corner (1,1).

\begin{aligned}\text{r}&=\sqrt{\left(\dfrac{-1}{6}-1\right)^{2}+\left(\dfrac{17}{6}-1\right)^{2}}\\[1.2em]&=\sqrt{\left(\dfrac{-7}{6}\right)^{2}+\left(\dfrac{11}{6}\right)^{2}}\\[1.2em]&=\sqrt{\dfrac{49}{36}+\dfrac{121}{36}}\\[1.2em]&=\sqrt{\dfrac{170}{36}}\\[1.2em]&=\sqrt{\dfrac{85}{18}}\\[1.2em]&=\dfrac{\sqrt{170}}{6}\end{aligned}

 

Step 5: Put it all together in an equation.

\left(x-\dfrac{-1}{6}\right)^{2}+\left(y-\dfrac{17}{6}\right)^{2}=\left(\dfrac{\sqrt{170}}{6}\right)^{2}

\left(x+\dfrac{1}{6}\right)^{2}+\left(y-\dfrac{17}{6}\right)^{2}=\dfrac{170}{36}

A LevelEdexcel

Example Questions

Side (-1,-1),(-3,-5):

\begin{aligned}\text{gradient}&=\dfrac{-5-(-1)}{-3-(-1)}\\[1.2em]&=\dfrac{-4}{-2}\\[1.2em]&=2\end{aligned}

So the gradient of the perpendicular bisector is \dfrac{-1}{2}

\begin{aligned}\text{midpoint}&=\left(\dfrac{-1-3}{2},\dfrac{-1-5}{2}\right)\\[1.2em]&=\left(\dfrac{-4}{2},\dfrac{-6}{2}\right)\\[1.2em]&=(-2,-3)\end{aligned}

So the perpendicular bisector passes through the point (-2,-3)

Now use all of this information to generate an equation in the form y=mx+c

y-y_{1}=m(x-x_{1})

 

y-(-3)=\dfrac{-1}{2}(x-(-2))

 

y+3=-\dfrac{1}{2}(x+2)

 

y+3=-\dfrac{1}{2}x-1

 

y=-\dfrac{1}{2}x-4

 

 

Side (-1,-1),(-6,2):

\begin{aligned}\text{gradient}&=\dfrac{2-(-1)}{-6-(-1)}\\[1.2em]&=\dfrac{3}{-5}\\[1.2em]&=-\dfrac{3}{5}\end{aligned}

So the gradient of the perpendicular bisector is \dfrac{5}{3}

\begin{aligned}\text{midpoint}&=\left(\dfrac{-1-6}{2},\dfrac{-1+2}{2}\right)\\[1.2em]&=\left(\dfrac{-7}{2},\dfrac{1}{2}\right)\end{aligned}

So the perpendicular bisector passes through the point \left(\dfrac{-7}{2},\dfrac{1}{2}\right)

Now use all of this information to generate an equation in the form y=mx+c

y-y_{1}=m(x-x_{1})

 

y-\dfrac{1}{2}=\dfrac{5}{3}(x-\dfrac{-7}{2})

 

y-\dfrac{1}{2}=\dfrac{5}{3}(x+\dfrac{7}{2})

 

y-\dfrac{1}{2}=\dfrac{5}{3}x+\dfrac{35}{6}

 

y=\dfrac{5}{3}x+\dfrac{19}{3}

 

 

Side (-3,-5),(-6,2):

\begin{aligned}\text{gradient}&=\dfrac{2-(-5)}{-6-(-3)}\\[1.2em]&=\dfrac{7}{-3}\\[1.2em]&=-\dfrac{7}{3}\end{aligned}

So the gradient of the perpendicular bisector is \dfrac{3}{7}

\begin{aligned}\text{midpoint}&=\left(\dfrac{-3-6}{2},\dfrac{-5+2}{2}\right)\\[1.2em]&=\left(\dfrac{-9}{2},\dfrac{-3}{2}\right)\end{aligned}

So the perpendicular bisector passes through the point \left(\dfrac{-9}{2},\dfrac{-3}{2}\right)

Now use all of this information to generate an equation in the form y=mx+c

y-y_{1}=m(x-x_{1})

 

y-\dfrac{-9}{2}=\dfrac{3}{7}(x-\dfrac{-3}{2})

 

y+\dfrac{9}{2}=\dfrac{3}{7}(x+\dfrac{3}{2})

 

y+\dfrac{9}{2}=\dfrac{3}{7}x+\dfrac{9}{14}

 

y=\dfrac{3}{7}x-\dfrac{27}{7}

Centre of circumcircle is where all three lines intersect.

3x+1=-4x-13

7x=-14

x=-2

y=3x+1

y=3(-2)+1

y=-6+1

y=-5

 

Check this works with the other perpendicular bisector:

y=-\dfrac{1}{3}(-2)-\dfrac{17}{3}

y=\dfrac{2}{3}-\dfrac{17}{3}

y=\dfrac{-15}{3}

y=-5

So all three perpendicular bisectors intersect at (-2,-5)

Find equation of the perpendicular bisector of the line through (-1,2) and (3,5).

\begin{aligned}\text{gradient}&=\dfrac{5-2}{3-(-1)}\\[1.2em]&=\dfrac{3}{3+1}\\[1.2em]&=\dfrac{3}{4}\end{aligned}

So gradient of perpendicular bisector is \dfrac{-4}{3}

\begin{aligned}\text{midpoint}&=\left(\dfrac{-1+3}{2},\dfrac{2+5}{2}\right)\\[1.2em]&=\left(\dfrac{2}{2},\dfrac{7}{2}\right)\\[1.2em]&=\left(1,\dfrac{7}{2}\right)\end{aligned}

So the perpendicular bisector goes through the point \left(1,\dfrac{7}{2}\right)

Now use all of this information to generate the equation of a line in the form y=mx+c:

y-y_{1}=m(x-x_{1})

 

y-\dfrac{7}{2}=\dfrac{-4}{3}(x-1)

 

y-\dfrac{7}{2}=-\dfrac{4}{3}x+\dfrac{4}{3}

 

y=-\dfrac{4}{3}x+\dfrac{4}{3}+\dfrac{7}{2}

 

y=-\dfrac{4}{3}x+\dfrac{29}{6}

 

Find equation of the perpendicular bisector of the line through (3,5) and (4,4).

\begin{aligned}\text{gradient}&=\dfrac{5-4}{3-4}\\[1.2em]&=\dfrac{1}{-1}\\[1.2em]&=-1\end{aligned}

So gradient of perpendicular bisector is 1

\begin{aligned}\text{midpoint}&=\left(\dfrac{3+4}{2},\dfrac{5+4}{2}\right)\\[1.2em]&=\left(\dfrac{7}{2},\dfrac{9}{2}\right)\end{aligned}

So the perpendicular bisector goes through the point \left(\dfrac{7}{2},\dfrac{9}{2}\right)

Now use all of this information to generate the equation of a line in the form y=mx+c:

y-y_{1}=m(x-x_{1})

 

y-\dfrac{9}{2}=x-\dfrac{7}{2}

 

y=x-\dfrac{7}{2}+\dfrac{9}{2}

 

y=x+1

 

Find centre by finding where the perpendicular bisectors intersect.

y=-\dfrac{4}{3}x+\dfrac{29}{6}

 

y=x+1

 

x+1=-\dfrac{4}{3}x+\dfrac{29}{6}

 

\dfrac{7}{3}x+1=\dfrac{29}{6}

 

\dfrac{7}{3}x=\dfrac{29}{6}-1

 

\dfrac{7}{3}x=\dfrac{23}{6}

 

x=\dfrac{3}{7}\times\dfrac{23}{6}

 

x=\dfrac{69}{42}

 

x=\dfrac{23}{14}

 

y=x+1

 

y=\dfrac{23}{14}+1

 

y=\dfrac{37}{14}

 

So centre is \left(\dfrac{23}{14},\dfrac{37}{14}\right)

 

Find the radius of the circumcircle by finding the distance from one corner to the centre.

Here we use corner (4,4).

\begin{aligned}\text{r}&=\sqrt{\left(\dfrac{23}{14}-4\right)^{2}+\left(\dfrac{37}{14}-4\right)^{2}}\\[1.2em]&=\sqrt{\left(\dfrac{-33}{14}\right)^{2}+\left(\dfrac{-19}{14}\right)^{2}}\\[1.2em]&=\sqrt{\dfrac{1089}{196}+\dfrac{361}{196}}\\[1.2em]&=\sqrt{\dfrac{1450}{196}}\\[1.2em]&=\sqrt{\dfrac{725}{98}}\\[1.2em]&=\dfrac{5\sqrt{58}}{14}\end{aligned}

 

Put it all together in an equation.

\left(x-\dfrac{23}{14}\right)^{2}+\left(y-\dfrac{37}{14}\right)^{2}=\left(\dfrac{5\sqrt{58}}{14}\right)^{2}

 

\left(x-\dfrac{23}{14}\right)^{2}+\left(y-\dfrac{37}{14}\right)^{2}=\dfrac{725}{98}

Additional Resources

MME

Exam Tips Cheat Sheet

A Level
MME

Formula Booklet

A Level

You May Also Like...

A Level Maths Revision Cards

The best A level maths revision cards for AQA, Edexcel, OCR, MEI and WJEC. Maths Made Easy is here to help you prepare effectively for your A Level maths exams.

£14.99
View Product

A Level Maths – Cards & Paper Bundle

A level maths revision cards and exam papers for Edexcel. Includes 2022 predicted papers based on the advance information released in February 2022! MME is here to help you study from home with our revision cards and practise papers.

From: £22.99
View Product

Transition Maths Cards

The transition maths cards are a perfect way to cover the higher level topics from GCSE whilst being introduced to new A level maths topics to help you prepare for year 12. Your ideal guide to getting started with A level maths!

£8.99
View Product